Use of Donor Human Milk and Maternal Breastfeeding Rates: A Systematic Review. (May 2016) - Williams, Thomas; Nair, Harish; Simpson, Judith; Embleton, Nicholas
The number of human milk banks is growing worldwide. The introduction of donor human milk (DHM) to neonatal units has been advocated as a strategy to promote maternal breastfeeding. However, concern has been raised that the introduction of DHM may actually lead to a decrease in maternal breastfeeding. To address this question, we conducted a systematic literature review of studies that assessed maternal breastfeeding rates before and after the introduction of DHM. We searched 7 electronic databases, carried out citation tracking, and contacted experts in the field. Where data for breastfeeding rates before and after the introduction of DHM were directly comparable, a relative risk was calculated. Our search identified 286 studies, of which 10 met the inclusion criteria. Definitions of patient populations and study outcomes varied, limiting meaningful comparison. Where possible, relative risks (RR) were calculated on aggregated data. The introduction of DHM had a significant positive impact on any breastfeeding on discharge (RR, 1.19; 95% confidence interval [CI], 1.06-1.35; P = .005) but none on exclusive maternal breastfeeding on discharge (RR, 1.12; 95% CI, 0.91-1.40; P = .27) or on exclusive administration of own mother's milk (OMM) days 1 to 28 of life (RR, 1.08; 95% CI, 0.78-1.49; P = .65). A single-center study demonstrated a significant decrease in the percentage of feeds that were OMM after the introduction of DHM. In conclusion, the available data demonstrate some evidence of positive and negative effects on measures of maternal breastfeeding when DHM is introduced to a neonatal unit.